Coping Style Mahasiswa Dalam Penyusunan Skripsi - Muliadi, Iwan; Ahmad Suriadi; Mahdia Fadhila (Jurnal Al-Husna, 2023)
Academic stress is defined as an individual's inability to deal with situations of pressure and demands that exist on him. When these pressures and demands are not resolved, it will result in the individual's psychological, cognitive and behavioral conditions in their academic activities. So that in overcoming this we need a coping style that can handle the pressure and demands that occur. In the definition of coping style itself is defined as a way for individuals to deal with problems in a way they like in dealing with stressful situations that occur to them. In the formation of this coping style, the individual cannot be separated from the behavioral, cognitive and motivational aspects. Therefore, the researcher wants to conduct research to find out and describe the level of academic stress that arises from the pressure on the demands that exist in the preparation of the thesis, the influence of coping styles, the tendency of coping styles, and factors that affect student coping styles in the preparation of thesis. This study also uses a survey method with a quantitative approach. The population in this study were all students of class 2016 at the State Islamic University of Antasari Banjarmasin, amounting to 1491 respondents with the determination of the sample of 229 respondents using the purposive sampling method with reference to the Isaac and Michael tables. Based on this research, the results obtained: 1) There is a level of student academic stress in the preparation of a final project of 77.56% in the medium level academic stress category. 2) There is a significant influence between coping style and student academic stress in the preparation of thesis final project at the State Islamic University of Antasari Banjarmasin with a significance level of 0.000 (p <0.05) giving an effective contribution of 32.9%. 3) There is a tendency of cognitive style coping in the preparation of the final thesis carried out by students of the State Islamic University of Antasari Banjarmasin by giving a contribution of 47.39%. 4) There are factors that influence the coping style in the preparation of the final project, such as internal and external factors.   Keywords: Coping style; academic stress; thesis preparation